PENERAPAN STRATEGI PEMBELAJARAN EKSPOSITORI UNTUK MENINGKATKAN MAHARAH AL ISTIMA’ PADA SISWA KELAS VII.10 DI MTSN 2 MAKASSAR - Muhammad Reski Mubarak Ranga; Rosmiati; Muhammad Syahrul; Abdul Qahar Zainal; Muh. Azhar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of expository learning strategies in improving the ability of maharah al-istima' (Arabic listening skills) of grade VII.10 students at MTsN 2 Makassar and identify supporting and inhibiting factors for its implementation. The research used the Kemmis and McTaggart model Class Action Research (PTK) which was carried out in two cycles with 36 students. Each cycle includes the stages of planning, implementation of actions, observation, and reflection. Data was collected through observation, interviews, documentation, and learning outcome tests. The results of the study showed a significant increase in students' listening skills. The average value increased from 42.80% in the pre-cycle to 65.75% in the first cycle and reached 84.25% in the second cycle. The percentage of learning completeness also increased from 22.22% to 86.11%. Qualitatively, students show more active participation, increased confidence, and better understanding of oral texts. The application of expository strategies is considered to be able to create an interactive learning atmosphere and facilitate the understanding of vocabulary and sentence structure. Based on these results, expository learning strategies have proven to be effective in improving students' maharah al-istima' and can be used as an alternative method of learning Arabic at the madrasah level.